2022
DOI: 10.1111/and.14443
|View full text |Cite
|
Sign up to set email alerts
|

A factor not to be ignored in post‐COVID ‐19 erectile dysfunction; psychological effect, a prospective study

Abstract: It was aimed to show the effect of anxiety and depression on erectile dysfunction seen after coronavirus disease‐2019 (COVID‐19). Between March and July 2021, the participants completed the International Index of Erectile Function, Beck Depression Inventory and Generalised Anxiety Disorder 7 forms at the beginning and after the 1st month of the disease. We investigated the psychological impact of COVID‐19 on the development of erectile dysfunction. The mean age of 156 male patients in the study was 54.74 ± 8.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In addition to the investigation of the direct effects on sexual function, there are also a number of studies that have underscored the role of poor mental health issues in this regard 8 . Many studies have also con rmed that the level of depression and the level of sexual dysfunction are directly correlated 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the investigation of the direct effects on sexual function, there are also a number of studies that have underscored the role of poor mental health issues in this regard 8 . Many studies have also con rmed that the level of depression and the level of sexual dysfunction are directly correlated 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The present study hypothesizes that COVID-19 patients may experience long-term cardio metabolic, endocrine and neurological complications which affect the normal physiology of erectile function could result in ED 16 . Different studies revealed that LC patients were associated with development of ED 12 , 17 . However, the underlying mechanism for development of ED in LC patients was not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Men with COVID-19 were 3.3 times as likely to experience ED ( Katz et al, 2022 ). Endothelial damage/dysfunction has been proposed as the fundamental pathophysiological mechanism of post-COVID-induced ED ( Sevim et al, 2022 ). Endothelial damage/dysfunction results from systemic endotheliitis, cellular death, increased inflammatory cytokines, residual activation of immune system, continuous stimulation of platelet activation and leukocyte adhesion, and decreased nitric oxide (NO) bioavailability ( Ambrosino et al, 2021 ).…”
mentioning
confidence: 99%
“…Endothelial damage/dysfunction results from systemic endotheliitis, cellular death, increased inflammatory cytokines, residual activation of immune system, continuous stimulation of platelet activation and leukocyte adhesion, and decreased nitric oxide (NO) bioavailability ( Ambrosino et al, 2021 ). It has been reported that such causes, in addition to other factors such as the severity of the COVID-19 condition, dread of death, and the length of the isolation period, produce anxiety and sadness, increasing the risk of ED ( Sevim et al, 2022 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation